"I Have Called You Friends": Toward a Pedagogy of Friendship in the Classroom. Issue 1 (May 2021) - Burt, Noel Forlini
Aelred of Rievaulx, a 12th-century Cistercian abbot, penned a powerful dialogue about the complexity of friendship titled Spiritual Friendship . Aelred's central claim is that friendship is the primary means through which Christ's love enters the world. In this article, I apply Aelred's insights on spiritual friendship to argue that Christ is the Friend at the center of the classroom. In particular, I suggest pedagogical practices that facilitate friendship as a Christian virtue, compelling learners to befriend one another, to befriend the subject, and to befriend God. Aelred does not suggest that everyone whom we love is to be a spiritual friend. Rather, those whom we choose to befriend are to be tested caringly and critically for their adherence to virtue. With the help of my ancient, theologian friends (Aelred, Augustine) and my friends who are leading voices in contemporary Christian pedagogy (David Smith, James K. A. Smith, Paul Griffiths), I aim to teach students to empathize with authors (and other learners) with whom they disagree, even to befriend them, even as they test whether those ideas are to be drawn into friendship.